SIMBOL BUDAYA DALAM NOVEL TIBA SEBELUM BERANGKAT KARYA FAISAL ODDANG (TINJAUAN SEMIOTIKA CHARLES SANDERS PIERCE) - Rismawati, Rismawati; Tang, Muhammad Rapi; Juanda, Juanda (Neologia: Jurnal Bahasa dan Sastra Indonesia, 2021)
This study aims to describe the cultural aspects in terms of icons, indexes, and symbols in Faisal Oddang's Tiba Before Berangkat novel by studying the semiotic theory of Charles Sanders Pierce. This research is a descriptive qualitative research type. The data source for this research is the novel Arrive Before Departure by Faisal Oddang. The data of this research are quotations containing cultural aspects based on a review of Charles Sanders Pierce's semiotic theory consisting of 3 signs. The data were collected using library techniques. The results showed that the cultural aspects in terms of icons, indexes and symbols are contained in Faisal Oddang's novel Tiba Before Berangkat.